2003
DOI: 10.3136/fstr.9.49
|View full text |Cite
|
Sign up to set email alerts
|

Microwave and Infrared Heat Processing of Honey and Its Quality

Abstract: Application of microwave and infrared radiation was explored for thermal processing of honey and its effect on the physico-chemical characteristics as well as the microbiological quality of honey were studied. Microwave heating provided a rapid means of achieving the desired level of yeast reduction with reduced thermal damage. Though different combinations of heating duration and microwave power intensity achieved the commercially acceptable level of yeast reduction in honey, heating for a shorter duration (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 7 publications
2
30
1
2
Order By: Relevance
“…The influence of different heat treatments on the quality parameters of various types of honey is well investigated, and it is known that it significantly impairs its quality (Hebbar et al 2003;Subramanian et al 2007;Bartáková et al 2011). Microwave heating, infrared heating, ultrasound processing, membrane processing, etc.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of different heat treatments on the quality parameters of various types of honey is well investigated, and it is known that it significantly impairs its quality (Hebbar et al 2003;Subramanian et al 2007;Bartáková et al 2011). Microwave heating, infrared heating, ultrasound processing, membrane processing, etc.…”
Section: Resultsmentioning
confidence: 99%
“…At the power level of 16.0 W/g, heating above 45 s resulted in the reduction of diastase activity to the level lower then minimum permissible value (DN < 8.0) (Hebbar et al 2003).…”
Section: Methodsmentioning
confidence: 93%
“…According to Hebbar et al (2003), heating times between 60 s to 90 s at the power levels of 6.3 W/g, 9.1 W/g, and 11.9 W/g, respectively, reduced diastase activity of honey by about 50% of its initial value. At the power level of 16.0 W/g, heating above 45 s resulted in the reduction of diastase activity to the level lower then minimum permissible value (DN < 8.0) (Hebbar et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The consequences of microwave treatment over honey properties, such as moisture content, acidity [Dranca & Oroian, 2013], HMF and enzyme activities [Kowalski et al, 2012], as well as over mould and yeasts [Hebbar et al, 2003] and bacteria spores have already been reported. Microwave radiation cannot be thought as simple heating from the inside; the E-fi eld would produce effects on the biological molecules affecting spore structure, different from those attributable only to heat [Celandroni et al, 2004].…”
Section: Introductionmentioning
confidence: 99%